Lets say we have following case:

Probability of bring a drunk driver = $0.10$

Probability of a drinking test coming positive = $0.30$

Probability of a drinking test coming negative, given the subject was not drunk = $0.90$

Then by Bayes theorem,

$$P(Not Drunk|Negative Test) = \frac{P(Negative Test|Not Drunk) \times P(Not Drunk) }{P(Negative Test)}.$$ Now, \begin{align} P(Negative Test|Not Drunk)& = 0.90\\ P(Not Drunk)& = 0.90\\ P(Negative test)& = 0.70 = (1 - Probability(Positive Test)) \end{align} Thus, $$P(Not Drunk|Negative Test) = (0.90 * 0.90) / 0.70 = 1.51.$$

As far as I understand, the probabilities shouldn't ever become more than 1 and above result is counterintuitive to me. Is this correct, if not where am I going wrong?


Your initial numbers are impossible.

To use your notation, and the Law of Total Probability:


Thus $$.7=.9\times.9 + P(Negative\,|\,NotDrunk)\times .1\implies P(Negative\,|\,NotDrunk)=-\frac {.11}{.1}=-1.1<0$$

Informally: say you had $100$ people. Then you have $90$ sober and $10$ drunk. Of the ninety, you tell us that exactly $9$ tests negative...so $81$ of those test positive. Thus the number of positive tests is at least $81$. Yet you claim that only $70$ test positive.


The problem is that your initial numbers cannot happen. This is because of the law of total probability which tells us that $P(A)=P(A|H_1)\cdot P(H_1) + P(A|H_2)\cdot P(H_2)$ if $H_1$ and $H_2$ are two oposing hypotheses. In your case, setting $A$ to be "Test is negative", $H_1$ to be "Driver is drunk"and $H_2$ to be "Driver is not drunk", you get

$$0.7 = P(A) = P(A|H_1)\cdot P(H_1) + P(A|H_2)\cdot P(H_2) = P(A|H_1)\cdot 0.1 + 0.9\cdot 0.9 = \\=P(A|H_1)\cdot 0.1 + 0.81$$

meaning that $P(A|H_1)$ is negative.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.